2008
DOI: 10.7326/0003-4819-148-7-200804010-00007
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of 2 Interventions for Liquid Aspiration on Pneumonia Incidence

Abstract: No definitive conclusions about the superiority of any of the tested interventions can be made. The 3-month cumulative incidence of pneumonia was much lower than expected in this frail elderly population. Future investigation of chin-down posture combined with nectar-thick liquid may be warranted to determine whether this combination better prevents pneumonia than either intervention independently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
275
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(286 citation statements)
references
References 30 publications
5
275
0
6
Order By: Relevance
“…These results are of great clinical relevance in light of published data indicating that patients who aspirated the more viscous 3,000 cP fluids and contracted pneumonia had hospital stays three times longer than those who aspirated the less viscous nectar fluid [12]. Longer hospital stays may have been precipitated by the 3,000 cP fluid being more viscous and having a higher yield stress and, therefore, being more difficult to clear from the airway than less viscous liquids [13].…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…These results are of great clinical relevance in light of published data indicating that patients who aspirated the more viscous 3,000 cP fluids and contracted pneumonia had hospital stays three times longer than those who aspirated the less viscous nectar fluid [12]. Longer hospital stays may have been precipitated by the 3,000 cP fluid being more viscous and having a higher yield stress and, therefore, being more difficult to clear from the airway than less viscous liquids [13].…”
Section: Discussionmentioning
confidence: 61%
“…However, significantly fewer patients rated honey barium as "easy" or "average" to swallow compared with the other levels of barium-a finding with important relevance for compliance when translated to treatment (e.g., dietary recommendations). Moreover, the 3 mo follow-up of subjects randomly assigned to use an intervention revealed that, of those hospitalized for pneumonia, subjects drinking thick honey liquids (3,000 cP) were hospitalized an average of 2 wk longer than subjects drinking nectar liquids (median = 18 vs 4 d, respectively) [12]. The thick honey barium may be more challenging to safely clear from the airway because the force required to move material, in this case ejecting from the airway, increases with higher viscosity and yield stress [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008; Robbins et al. 2008). In addition, thickening liquids can affect the patient's hydration status if they dislike the thickening (Robbins et al.…”
Section: Discussionmentioning
confidence: 99%
“…Only articles on the effects of therapy for oropharyngeal dysphagia in Parkinson's disease were included. Studies describing heterogeneous subject populations that included patients with Parkinson's disease and patients with other neurologic diseases were excluded [6], except those studies that presented both pre-and posttreatment data per subgroup [7]. Patients receiving deep brain stimulation were excluded.…”
Section: Methodsmentioning
confidence: 99%